How do cold water biota arrive in a tropical bay near Rio de Janeiro, Brazil? - Stevenson, Merritt R.; Brito, Dimas Dias [UNESP]; Stech, Jose L.; Kampel, Milton (Elsevier B.V., 1998)
Previous ecological studies on foraminifera and ostracoda from the tropical Sepetiba Bay, located in the southern part of the State of Rio de Janeiro, Brazil, have noted the presence in this area of some cool water taxons typical of the Argentine continental platform. These studies have proposed that parcels of these temperate waters with their associated biological indicators are advected northward along the platform, penetrating into some tropical entrances of the southeast coast of Brazil. In the present study, ecological data (foraminifera, ostracoda and microbivalves), are used together with information obtained by satellite tracked drifting buoys and digital thermal imagery obtained from NOAA satellites to indicate the path taken by these high latitude species along the southern Brazilian coast to arrive in the Sepetiba Bay, near the city of Rio de Janeiro. Our general conclusion is that biotic elements native to the colder, less saline marine waters seen to the south of Brazil have been and are being advected northward along the inner part of the continental platform to about 22 degrees S. Water parcels containing this biota may, in a sporadic fashion, enter into the tropical Sepetiba Bay. The passage of meteorological fronts through the region is considered to be an important if not the principal mechanism for the sporadic entry of the cool water into the Southern Coastal Entrance of the State of Rio de Janeiro. (C) 1998 Elsevier B.V.s Ltd. All rights reserved.